Genotoxicidade, atividade proliferativa e análise fitoquímica dos extratos aquosos e do óleo de Origanum majorana L. - Baldoni, Micheli Bortoluzzi (2017)
Medicinal plants are culturally used by the Brazilian population in curing and treating diseases and the fact that Brazil is rich in biodiversity favors this practice. Among the medicinal plants used are the marjoram (Origanum majorana L.) belonging to the family Lamiaceae. This species is commonly used as aromatic, analgesic, antioxidant, antiseptic, digestive, expectorant and in cooking. The objective of the present work was to analyze the genotoxicity and proliferative activity of the aqueous extracts and the oil of the leaves of marjoram on the cell cycle of Allium cepa, besides to verify the phytochemical composition through Chromatography. The aqueous extracts were prepared from the marjoram leaves that were grown in different environments (field and greenhouse) and with two drying methods (natural shade and microwave oven). Fresh leaves were used to extract essential oil. The evaluation of genotoxicity and proliferative activity through the Allium cepa test were conducted in the laboratory through a completely randomized design with 13 groups of bulbs with 5 replicates. The treatments were composed of distilled water, glyphosate 2%, infusion of marjoram leaves with concentrations of 6 and 12 g L-1, essential oil diluted to 0.075% and ethyl alcohol. These treatments were divided in two methods of drying the leaves: at room temperature (natural) and in microwave oven, in order to compare the phytochemical composition of the aqueous extracts. For the genotoxic analysis and the proliferative capacity, slides were prepared by the technique of crushing the meristematic region and staining with acetic orcein 2%, allowing the observation of the different phases of the mitotic division during the cell cycle. The results obtained by the Allium cepa test demonstrate that treatments with marjoram infusions and oils have an antiproliferative and genotoxic effect. 0.075% marjoram oil has antiproliferative activity and genotoxic potential. Chromatographic analysis indicated that the major component of the essential oils of marjoram in both culture environments was Terpinene-4-ol, and the concentration of this component was higher in greenhouse cultivation, and in the aqueous extracts the major component was chlorogenic acid. When it were produced in the field there was the reduction of this component. The treatment interaction within each culture environment in relation to the mitotic index shows a difference between the concentrations in the field crop and not between the concentrations in the greenhouse cultivation. The treatment interaction within each drying method for the mitotic index at concentrations of 6 g.L-1 and 12 g.L-1 showed no differences.